2023
DOI: 10.21203/rs.3.rs-3197499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional intelligence as a predictor of job satisfaction among midwives in Northern Iran:  a cross-sectional study

Fatemeh Zolfaghary,
Hajar Adib-Rad,
Hajar Pasha
et al.

Abstract: Background Emotional Intelligence (EI) is an important skill for midwives. Our study aimed to understand EI as a Predictor of Job Satisfaction among Midwives. Methods This descriptive-correlational study was conducted on 143 employed midwives in maternity wards of government and private hospitals, as well as healthcare centers in Iran. The data were collected using demographic-fertility Characteristics, emotional intelligence, and job satisfaction questionnaires. For the assessment of EI, the Bar-On's Emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, in the context of midwifery, the correlation of high self-efficacy with high emotional intelligence seems critical as it might contribute significantly to the effectiveness and satisfaction levels of midwives in their professional roles. An unpublished study focused on midwives in Northern Iran revealed that their job satisfaction and emotional intelligence were moderate on average [ 51 ], and it also highlighted that higher levels of emotional intelligence were associated with increased job satisfaction among midwives. This correlation included improved inter- and intrapersonal skills and adaptability, suggesting that as midwives’ abilities to understand and manage their own emotions and adapt to changing circumstances improve, their satisfaction with their job also increases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the context of midwifery, the correlation of high self-efficacy with high emotional intelligence seems critical as it might contribute significantly to the effectiveness and satisfaction levels of midwives in their professional roles. An unpublished study focused on midwives in Northern Iran revealed that their job satisfaction and emotional intelligence were moderate on average [ 51 ], and it also highlighted that higher levels of emotional intelligence were associated with increased job satisfaction among midwives. This correlation included improved inter- and intrapersonal skills and adaptability, suggesting that as midwives’ abilities to understand and manage their own emotions and adapt to changing circumstances improve, their satisfaction with their job also increases.…”
Section: Discussionmentioning
confidence: 99%